Como os alunos de bateria do curso de Licenciatura em Música da UFPB percebem o desenvolvimento de sua aprendizagem instrumental. - Costa, Fábio Lima da (2023)
The process of musical learning is a recurring theme in a musician's life, even if they don't consciously perceive it in a systematic way. Given this reflection, the objective of this study was to understand how undergraduate drum students at UFPB (Federal University of Paraíba) perceive the development of their learning. The specific objectives were to identify the main characteristics of the undergraduate drum education at UFPB, to identify the profiles of drum students, to analyze the paths of musical education taken by drum students, and to examine how these students organize their drum studies in the music education program. This study aimed to comprehend how drum students in the music education program at UFPB perceive the development of their learning as the general objective. Regarding the specific objectives, we aimed to identify the main characteristics of the undergraduate drum education at UFPB, to identify the profiles of drum students, to analyze the paths of musical education taken by drum students, and to examine how these students organize their drum studies in the music education program. To achieve the set objectives, a qualitative research approach was adopted, and the data was obtained through exploratory bibliographic and descriptive research, using a questionnaire. The questionnaire indicated that, in general, the participants have some difficulty in assessing their own performance. The process through which students evaluate their own performance is important because it allows individuals to have an active role in their own learning process.